Odpowiedzi

2009-12-13T19:54:49+01:00
5x +0,2=4
5x = 3,8 /:5
x=0,76

3x + 15,4 - 2x = 3,4
x+15,4 = 3,4 / -15,4
x= - 12

7x = 42 /:7
x = 6

3x - 6 = 15 /+6
3x = 21 /:3
x=7

x+ 5 = 12 /-5
x=7

12 = 4x +9 /-9
3 = 4x
x=0,75
1 5 1
2009-12-13T20:29:29+01:00
5x +0,2=4
5x = 3,8 /:5
x=0,76

3x + 15,4 - 2x = 3,4
x+15,4 = 3,4 / -15,4
x= - 12

7x = 42 /:7
x = 6

3x - 6 = 15 /+6
3x = 21 /:3
x=7

x+ 5 = 12 /-5
x=7

12 = 4x +9 /-9
3 = 4x
x=0,75
1 5 1
Najlepsza Odpowiedź!
2009-12-14T01:48:43+01:00
5x + 0,2 = 4
5x = 3,8 /:5
x = 0,76


3x + 15,4 - 2x = 3,4
x = 3,4 - 15,4
x= -12


7x = 42 /:7
x = 6

3x - 6 = 15
3x = 15 + 6
3x = 21 /:3
x = 7

x+ 5 = 12
x = 12 - 5
x = 7

12 = 4x +9
12 - 9 = 4x
3 = 4x /:4
x=3/4

POZDRAWIAM :)